2000
DOI: 10.1051/forest:2000106
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nutrients of beech (Fagus sylvatica) bark in relation to frost sensitivity and soil treatments in southern Sweden

Abstract: -Concentration of nutrients and balance between nutrients in trees can affect tree vitality, and are dependent on soil conditions and atmospheric deposition. The aim of this investigation was to survey the concentration of nutrients in beech bark and to look for relationships with the frost sensitivity of the bark. Beech trees with bark lesions were compared to undamaged beech trees on five experimental sites with control plots, plots treated with nitrogen, ash or lime. Trees treated with lime had increased Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…In the bark of mature beech trees (Fagus sylvatica) growing on acidic soils in Southern Sweden, the range of N concentrations also was slightly higher (5.5-7.0 mg·g -1 D.M. ; [21]). In our investigation, the decrease in N concentration in the bark of the RD trees may have been caused by reduced N uptake as a consequence of decreased fine root production after defoliation -a reduction in fine-root biomass after defoliation of Q. robur has been found, e.g., by Block et al (1995) [7] and Gieger and Thomas (2002) [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the bark of mature beech trees (Fagus sylvatica) growing on acidic soils in Southern Sweden, the range of N concentrations also was slightly higher (5.5-7.0 mg·g -1 D.M. ; [21]). In our investigation, the decrease in N concentration in the bark of the RD trees may have been caused by reduced N uptake as a consequence of decreased fine root production after defoliation -a reduction in fine-root biomass after defoliation of Q. robur has been found, e.g., by Block et al (1995) [7] and Gieger and Thomas (2002) [14].…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by weathering of the calcareous bedrock. High values were also found in other studies on a range of soils, with Ca concentrations in oak stem bark of about 30 to 50 times higher than in the sapwood of trees growing on podzol to dystrochrept soil (André andPonette 2003, Whittaker et al 1979), and about 20-30 mg g -1 on fertilized cambic podzols and dystric cambisols in Fagus sylvatica in southern Sweden (Jönsson 2000). In our study, Fagus sylvatica showed significantly higher Ca concentrations in the stem bark with increasing tree species diversity and increasing exchangeable Ca stocks in the soil.…”
Section: Nutrient Concentrations In Different Tree Compartmentssupporting
confidence: 58%
“…It can be assumed that the requirements of N. ditissima for mineral and nitrogen nutrition that is provided to this fungus by longer annual shoots with greater growth can play an important role in this correlation. Similarly, Jönsson (2000) studied the soil treatment effects on bark lesions and frost sensitivity of beech in relation to the application of different treatments in beech stands (liming, wood ash, nitrogen). She reported that bark lesions on beech are mostly caused by frost damage and/or insect and fungal infections.…”
Section: Discussionmentioning
confidence: 99%